Law on Lawyers - The National Assembly (2006)
This Law provides for the principles, conditions, scope and forms of professional practice by, as well as criteria, rights and obligations of, lawyers, law-practicing organizations and socio-professional organizations of lawyers; the management of law practice and professional practice by foreign law-practicing organizations and foreign lawyers in Vietnam.